Impact of Capitalization on the Profitability of Nepalese Commercial Banks - Upreti, Shristi; Bist, Diwakar (Nepalese Journal of Economics, 2024)
This study examines the impact of capitalization on the profitability of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are market capitalization, capital adequacy ratio, total deposit, debt to equity ratio, book value per share and non-performing loans. The study is based on secondary data of 16 commercial banks with 112 observations for the study period from 2015/16 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of the impact of capitalization on the profitability of Nepalese commercial banks. The study showed that market capitalization has a positive impact on return on assets and return on equity. It indicates that increase in market capitalization leads to increase in return on assets and return on equity. Similarly, capital adequacy ratio has a positive impact on return on assets and return on equity. It indicates that higher the capital adequacy ratio, higher would be the return on assets and return on equity. Likewise, total deposit has a positive impact on return on assets and return on equity. It indicates that increase in total deposits leads to increase in return on assets and return on equity. Further, debt to equity ratio has a negative impact on return on assets and positive impact on return on equity. It indicates that increase in debt to equity ratio leads to increase in return on assets and decrease return on equity. In addition, book value per share has a positive impact on return on assets and negative impact return on equity. It indicates that higher the book value per share, higher would be the return on assets and lower would be return on equity. Moreover, non-performing loan has a negative impact on return on assets and return on equity. It indicates that higher the non-performing loan, lower would be the return on assets and return on equity.